Hayek Reads the Literature on the Emergence of Norms - Luciano Andreozzi (Max Planck Institute for Research into Economic Systems, 2005)
Hayek's approach to cultural and institutional evolution has been frequently criticized because it is explicitly based on the controversial notion of (cultural) group selection. In this paper this criticism is rejected on the basis of recent works on biological and cultural evolution. The paper's main contention is that Hayek employed group selection as a tool for the explanation of selection among several equilibria, and not as a vehicle for the emergence of out of equilibrium behavior (i.e. altruism). The paper shows that Hayek's ideas foreshadowed some of the most promising developments in the current literature on the emergence of norms.
Keywords: B31; B41; 330; Hayek; cultural evolution; group selection; social norms; Soziale Norm; Institutionelle Infrastruktur; Methodologischer Individualismus; Evolutionsökonomik; Friedrich A. von Hayek